Pre-school Children Investigatory Activities in the Environment Created by Adults - Grava, Jana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In order to create one’s own model of world cognition, a child acquires information from the environment created around him/her, which ensures the development of child’s explorative activity by arousing interest and curiosity, that later, in its turn, create the basis for learning motivation. Child’s explorative activity is a means to cognize the world that has been essentially influenced by the environment created by adults. The problem arises, if adults do not understand child’s activities that develop understanding about the world around. As a result, unreasonable criticism and evaluation from the adult’s point of view can be observed. Thus, it is important to clarify how the environment created by adults influence explorative activity of a child and what are the facilitating and delaying factors. The article reveals the theoretical findings based on pedagogical and psychological research (M.Osorin, H.Gudjon, R.Hart, I.Malkin-Pih, N.Podiakov, T.Amabile, D.Liegeniece) on explorative activity of preschool age children, as well as the pedagogical observation of the author.